Extended Producer Responsibility (EPR) in electronic industry / Theepa Subbramaniam - Subbramaniam, Theepa (2013)
Electronic waste has been expanding rapidly in developing Asia and is predicted to grow to 12 million tonnes by 2020. The environmental and health issues resulting from poor management of this waste have become a concern among policy makers. A number of developing countries in Asia have been inspired by policy developments in Organization for Economic Cooperation and Development (OECD) countries, and have drafted legislations based on the principle of Extended Producer Responsibility (EPR). E-waste has been one of the fastest-growing waste streams in Malaysia since it is increasing at 40% each year, owing to an increase in consumption of electrical and electronic equipment.EPR has been one of the most attractive E-waste management policies at different levels of society. A number of industrialized countries have established EPR systems for a wide range of electrical and electronic equipments(e-products), vehicles, household hazardous wastes, and etc.However, experiences from OECD and European countries have shown that effective implementation of EPR can be challenging despite being simple.Therefore, this study is aimed to look at the adoption of EPR in Electronic Industry in Malaysia and to study the level of awareness and knowledge among the public on EPR and E-waste.The study also seeks to assess the level of awareness among the management staff of the industry and the practice of EPR among 10 selected electronic companies. Expertchoice software was used for this evaluation. The research methodology for this study covers questionnaires/survey administered to the public and interview sessions. Knowledge and awareness of public towards EPR and take-back programme have been significantly low. From the 200 respondents interviewed, 71% were not aware on such practices in Malaysia. Respondents prefer campaigns and exhibitions as their suggestive measures to increase level of awareness on EPR and take-back. All 10 companies interviewed have been practicing EPR efficiently. Data generated from Expertchoice show that Company F prioritizes Environmental stewardship (21%), Company G in Product Innovation (19%), Company B in Take-back (22%), Company E and H in Green marketing(21%), and Company C and D in Cost savings (22%) towards an effective EPR practice. As a conclusion, Company A and B have been the best in adopting the EPR practice based on all factors evaluated. Level of awareness and knowledge on EPR among management staff of the industry, as well as, public is at a moderate level. The education background and exposure in higher institutions have played an important role in educating the respondents on issues related to EPR and E-waste.